2021
DOI: 10.2298/sarh210506053s
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on suicide attempts in the Republic of Serbia

Abstract: Introduction/Objective. Previous studies suggest that number of suicides and suicide attempts will increase due the COVID-19 pandemic. The aim of this study was to investigate the impact of the COVID-19 pandemic on the frequency and characteristics of suicide attempts in the Republic of Serbia. Methods. The study observed two periods: the period from March to August 2020 (the COVID period) and the same period of the previous year (the non-COVID period). The observation during the mentioned p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…This worsening has been related to the symptoms of the infection but also to other preventable social circumstances, such as the loss of therapeutic interventions, the loss of employment, and low financial income [36,37]. The research shows that the increase in suicide rate in psychiatric patients during public health crises, such as pandemics, is connected with the fear of getting sick, becoming a burden to the family and a fear for life, anxiety, social isolation and distress [38]. It is well documented that the social support level in psychiatric patients plays a significant role in maintaining remission and is inversely related to suicidal relapse [20,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This worsening has been related to the symptoms of the infection but also to other preventable social circumstances, such as the loss of therapeutic interventions, the loss of employment, and low financial income [36,37]. The research shows that the increase in suicide rate in psychiatric patients during public health crises, such as pandemics, is connected with the fear of getting sick, becoming a burden to the family and a fear for life, anxiety, social isolation and distress [38]. It is well documented that the social support level in psychiatric patients plays a significant role in maintaining remission and is inversely related to suicidal relapse [20,39].…”
Section: Discussionmentioning
confidence: 99%
“…The feeling of fear of COVID-19, especially the fear of getting sick and dying, is significantly associated with a perceived level of distress [37][38][39][40]. The lowest and highest scores on the FCV-19S scale are recorded in East Asia and Spain (16 +/− 6; 18 +/− 5) and Australia (19 +/− 6), with a special risk for people who are younger, female, unemployed and students, as well as health care workers, while older people, men and those with better education showed lower values on the Fear of COVID-19 Scale [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Serbia reported on an increasing number of suicide attempts, as well as other forms of suicidal behaviour in the previous two years, when the pandemic was at its peak and most threatening to people (23)(24)(25). Besides, an elevated level of stress was also recorded, together with the increased level of anxiety, depression, fear of losing someone, loneliness, among the general population, but also the population of people with pre-existing mental health issues (3,6).…”
Section: Suicidalitymentioning
confidence: 99%
“…On the other hand, a meta-analysis that has synthesised international reports on suicidal behaviours in the recent years, speaks in favour of an upward trend of suicidal ideation and suicide attempts during the COVID-19 pandemic, with the suicide rate remaining stable (44). A study conducted in Serbia reports that the Psychiatric Clinic "Dr Laza Lazarević" had more suicide attempts registered in the period between March and July 2020 in comparison with the same period in the previous year (23). A similar study was carried out at the Psychiatric Clinic of the University Clinical Centre of Niš, which reported significantly more suicide attempts in 2020 than in prior years (24).…”
Section: The Pandemic and Suicidalitymentioning
confidence: 99%
“…This viral disease spread across the globe, leading to the one of the largest outbreaks in recent years which resulted in COVID-19 being a major public health burden [2]. The clinical presentation of SARS-CoV-2 infection varies from asymptomatic to severe and critical illness with multiorgan involvement [3]. Growing evidence suggests that a key role in the pathogenesis and determining the severity of COVID-19 is played by the immune system of the infected host [4].…”
Section: Introductionmentioning
confidence: 99%